Pengaruh Harga dan Keragaman Menu terhadap Minat Beli Ulang Konsumen di Koperasi Squid Curug - Feti Fatonah; Fadhil Fadlurrahman; Muhammad Farhan; Elisabeth Vania; Mahardika Yoga (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
In the world of entrepreneurship, every business strives to achieve success in running its operations. The increasingly intense competition today demands that entrepreneurs be more intelligent and creative in attracting consumer attention and interest1. This condition is also experienced by Koperasi SQUID Curug, one of the culinary businesses operating within the environment of the Indonesian Aviation Polytechnic (Politeknik Penerbangan Indonesia Curug). To maintain its business sustainability, the cadets need to understand the factors that influence consumer behavior, particularly those related to price and menu variety.This study aims to understand the influence of price and menu variety on consumers repurchase intention at Koperasi SQUID Curug, which is managed by the cadets of the Indonesian Aviation Polytechnic Curug. The research employs a descriptive qualitative approach with data collected through in-depth interviews, direct observation, and documentation involving consumers. The collected data were analyzed descriptively by focusing on the meaning and underlying reasons behind consumers’ purchasing decisions.The results show that the perception of affordable prices and continuously updated menu variations are the main factors driving repurchase intention at Koperasi SQUID. In addition, environmental factors such as strategic location, friendly service, and limited meal times in the cadets’ dining hall also influence purchasing decisions.In conclusion, the management of Koperasi SQUID needs to maintain a pricing strategy that aligns with the purchasing power of cadets, continuously innovate in menu offerings, and strengthen internal promotions to increase awareness and consumer interest within the campus environment.